2021
DOI: 10.1002/ceat.202000428
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Droplets in Double T‐Shaped Microchannels with Necked Structures

Abstract: Microfluidic droplets are widely applied in various fields such as biomedicine, aerospace, energy utilization, and chemical engineering due to their advantages of large specific surface area, uniform size, stability, and easy control. The double T‐shaped microchannel has the characteristics of rapid preparation of microdroplets with controllable size and good uniformity. Through 3D numerical simulation, the influence of the constriction structure of the microchannel on the formation of droplets was studied qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Microdroplets, the scale-down analytical platforms, are commonly used in the fields of analytical chemistry [ 1 ], biology [ 2 ], material synthesis [ 3 ], and so on. Understanding the impacting mechanism between a liquid-in-air droplet and an immiscible aqueous solution is important and helpful for lots of applications, such as biofabrication through inkjet printing [ 4 , 5 ] and droplet encapsulation [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] for drug delivery [ 14 , 15 ], PCR reaction [ 16 , 17 ], and preparation of Janus droplets [ 18 ] or double-emulsions [ 19 , 20 ]. When the oil droplet impacts with another immiscible aqueous solution, it will transiently knock a crater on the surface of the aqueous solution and lead to the floating, bouncing, jetting, or splashing of the solution [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microdroplets, the scale-down analytical platforms, are commonly used in the fields of analytical chemistry [ 1 ], biology [ 2 ], material synthesis [ 3 ], and so on. Understanding the impacting mechanism between a liquid-in-air droplet and an immiscible aqueous solution is important and helpful for lots of applications, such as biofabrication through inkjet printing [ 4 , 5 ] and droplet encapsulation [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] for drug delivery [ 14 , 15 ], PCR reaction [ 16 , 17 ], and preparation of Janus droplets [ 18 ] or double-emulsions [ 19 , 20 ]. When the oil droplet impacts with another immiscible aqueous solution, it will transiently knock a crater on the surface of the aqueous solution and lead to the floating, bouncing, jetting, or splashing of the solution [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[36,37] For example, Xu et al [38] used four kinds of surfactants (i.e., KH-570, KH-550, Zinc stearate, and Sodium stearate) to modify the Wo fibers and found that KH-570 modified sample possessed the maximum contact angle and activation index. Zhang [39] compared the effects of surface modification of Wo with KH-570 and titanate coupling agent JN-114 and demonstrated better interface integration between KH-570-fillers and PP matrix through SEM images. Stearic acid was used by Salas-Papayanopolos et al as a modifier for the PP-Wo system.…”
Section: Introductionmentioning
confidence: 99%
“…The generation process of microdroplets in the T-inlet microchannel device is jointly affected by multiple parameters, among which the fluid property parameters include flow rate ratio, interfacial tension, internal wettability of the microchannel [24,25], etc. The geometrical parameters include the angle between the two phases of the T-junction microchannel, aspect ratio of the inlet, width ratio of different entry channels [26][27][28][29], etc. In experimental studies, researchers often change the flow rate ratio by altering the two-phase fluid flow rate, the wettability inside the microchannel by attaching a chemical coating to the surface of the microchannel, and use of chemical active agents to vary the interfacial tension of the two-phase fluid.…”
Section: Introductionmentioning
confidence: 99%